TRANSFORMASI PEMASARAN AGRIBISNIS DI ERA DIGITAL: ANALISIS LITERATUR DAN DATA SEKUNDER DI INDONESIA - Hera Wati; Arief Putra Johavi Damanik, Rama Ardiansiah Tumangger, Austin bein Beryl Jahran Saragih, Richard Jos; Lokot Muda Harahap (CV. Adiba Aisha Amira, 2025)
The transformation of agribusiness marketing in the digital era has become a strategic issue in the development of the agricultural sector in Indonesia. One of the main obstacles to agribusiness is the long distribution chain, which results in low profit margins for farmers. The development of information and communication technology has opened up opportunities for the digitalisation of marketing, enabling farmers and MSMEs to expand their markets, improve efficiency, and improve their bargaining position. This study aims to analyse literature related to agribusiness digital marketing, examine secondary data from the Central Statistics Agency (BPS), and identify opportunities, challenges, and supporting strategies for agribusiness marketing transformation in Indonesia. The methods used are literature study and secondary data analysis. The literature was obtained from Sinta and international indexed journals, while the secondary data came from official BPS publications, such as the 2023 Agricultural Census, 2023 Agricultural Indicators, and 2023 E- Commerce Statistics. The results of the study show that the application of digital marketing through social media, e-commerce, marketplaces, and digital content can increase farmers' income by 30–40% and expand market reach threefold compared to conventional systems. BPS data reinforces these findings by recording 3.82 million active e-commerce businesses in Indonesia and a 42% adoption rate of digital technology by young farmers, which is higher than the national average of 34%. However, obstacles still include low digital literacy, limited rural infrastructure, capital, and logistical constraints. In conclusion, digital transformation has the potential to strengthen the competitiveness of Indonesian agribusiness, but it requires policy support, digital literacy training, multi-stakeholder collaboration, and product branding to ensure sustainability.